2017
DOI: 10.1007/s00339-017-0977-3
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the bulk and surface properties of liquid Zn–Cd alloys

Abstract: The effects of temperature on the bulk and surface properties of liquid Zn-Cd alloys have been theoretically investigated, using a combination of self association model, Darken's thermodynamic equation for diffusion, empirical model for viscosity and a statistical mechanics model. The results from this study show that change in temperature resulted in cross-over effects in bulk and surface properties. We also found that with an increase in temperature, a pronounced asymmetry of viscosity isotherm is significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…3 shows the demixing tendencies in Zn-Bi liquid alloy at all the temperatures albeit at varying degrees. This is an indication that Zn-Bi liquid alloys are homocoordinated and that the homocoordination which is strong is indicated by the relatively high peak at various temperatures when compared with weakly homocoordinated alloys like Zn*Cd liquid alloys [24]. It should be noticed that there is a relatively large reduction in the peak value of S xx (0) as the temperature increased from 923 to 1023 K. This trend in the reduction of the peak value of S xx (0) suggests some form of the reduction in the demixing tendencies of this alloy with an increase in temperature.…”
Section: Concentration Fluctuationmentioning
confidence: 91%
See 1 more Smart Citation
“…3 shows the demixing tendencies in Zn-Bi liquid alloy at all the temperatures albeit at varying degrees. This is an indication that Zn-Bi liquid alloys are homocoordinated and that the homocoordination which is strong is indicated by the relatively high peak at various temperatures when compared with weakly homocoordinated alloys like Zn*Cd liquid alloys [24]. It should be noticed that there is a relatively large reduction in the peak value of S xx (0) as the temperature increased from 923 to 1023 K. This trend in the reduction of the peak value of S xx (0) suggests some form of the reduction in the demixing tendencies of this alloy with an increase in temperature.…”
Section: Concentration Fluctuationmentioning
confidence: 91%
“…It has been reported that transport properties such as diffusivities of metals in the liquid state are needed for many metallurgical processes [24]. Also, from the practical point of view, the viscosity is reported to be one of the key parameters for the design and optimization of metallurgical processes [25].…”
Section: Diffusionmentioning
confidence: 99%
“…0.2484 at 𝐶𝐶𝑃𝑃𝑃𝑃= 0.8 and then increases. This indicates that the possibility of phase separation is maximum around 𝐶𝐶𝑃𝑃𝑃𝑃= 0.8 [16]. It should be pointed out that no experimental data for of PbSn system at 1050 K have been introduced in Fig.…”
Section: Transport Propertiesmentioning
confidence: 94%
“…In self association model, the constituent atoms are supposed to be comparable in size (or volume) which may be applicable for Pb and Sn atoms. For four decades, self association model [13] has been adequately applied [14][15][16][17] to explain the bulk and surface properties of binary liquid alloys such as CdGa, AlSn, SnTl, CdZn, BiSn etc. Section-2 deals with the analytical equations for the thermodynamic, structural, surface and transport functions of a binary system in molten state in the framework of self association model.…”
Section: Introductionmentioning
confidence: 99%